Hyperuricemia research progress in model construction and traditional Chinese medicine interventions - Zhou, Hongyan; Yang, Jingyi; Yuan, Xiaoqing; Song, Xinyu; Zhang, Xingcai; Cao, Ting; Zhang, Jiayu (Frontiers in Pharmacology, 2024)
Hyperuricaemia (HUA), a severe metabolic disease derived from purine metabolism disorder, will leads to abnormally increased serum uric acid (SUA) levels in the body. Studies have shown that HUA is highly related to gout, hypertension, diabetes, coronary heart disease, chronic kidney diseases and so on. Traditional Chinese Medicine (TCM) shows excellent talent in treating HUA due to because of its their unique advantages of multi-metabolites and multi-targets, and now it is on the cusp of screening uric acid (UA)-lowering TCM with excellent efficacy and low side-effects based on established HUA models. This work summarises HUA disease models for efficacy evaluation and their corresponding advantages and limitations. Besides, applications of TCM in HUA treatment have also been discussed in detail. This paper reveals recent research progress on HUA in the construction of constructing evaluation models and the systematic intervention of TCM. It will undoubtedly provide a scientific reference for establishing the HUA model and provide a thinking for TCM-related HUA studies in the future.